Weight Stigma and Its Association With Nutritional Status in Students of Health Careers in a Private University in the Region of Ñuble, Chile: Estigma de peso y su asociación con el estado nutricional en estudiantes de carreras de salud en una universidad privada en la región de Ñuble, Chile | 体重污名及其与智利Ñuble地区一所私立大学健康专业学生营养状况的关联 - Retamal, Kevin (2024)
Introduction: Obesity and overweight constitute global public health challenges, negatively impacting more than one billion people. They are accompanied by significant psychological and social consequences, including the stigma associated with weight, with severe repercussions on mental and physical well-being. Health professionals are directly involved with this problem; however, few studies address weight stigma in Chile. Objective: To relate nutritional status (BMI) and the level of weight stigma in university students of health careers in the region of Ñuble, Chile. Methodology: Observational design of correlational and cross-sectional scope. The GAMS-27 scale was applied to assess weight stigma and BMI to evaluate the nutritional status of 156 students of health careers. Chi2 tests of independence and binary logistic regression were applied to evaluate the association between the variables, with the R statistical package version 4.3.0. Results: A statistically significant association was found between weight stigma and nutritional status (p=0.0145). Presenting normal BMI (p=0.0163) and being female (p=0.0156) were associated with a higher probability of presenting weight bias. Conclusions: The present study identified a statistically significant association between weight stigma and nutritional status in college students. It is vital to promote education regarding weight stigma in college students to avoid bias and improve respect for future users.